2010
DOI: 10.1177/0741088310378217
|View full text |Cite|
|
Sign up to set email alerts
|

Rethinking Composing in a Digital Age: Authoring Literate Identities Through Multimodal Storytelling

Abstract: In this article, the authors engage the theoretical lens of multimodality in rethinking the practices and processes of composing in classrooms. Specifically, they focus on how learning new composing practices led some fifth-grade students to author new literate identities—what they call authorial stances—in their classroom community. Their analysis adds to the current research on the production and analysis of multimodal texts through an analysis of the interrelationships between multimodal composing processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(144 citation statements)
references
References 26 publications
7
123
0
6
Order By: Relevance
“…They all knew that outside the classroom students were exposed to new texts and resources, whereas in the traditional classroom paper and pencil were the primary tools used for the purpose of conveying messages. These findings are consistent with those of a number of researchers (Hughes & Narayan, 2009;Thompson, 2008;Vasudevan, Schultz, & Bateman, 2010); Specifically, the teachers' comments revealed their perception that students were more likely to participate actively in collaborative projects and reflective learning practices, demonstrating the essential features of willingness and enthusiasm.…”
Section: Teaching Multimodal Composition and Affective Engagementsupporting
confidence: 80%
“…They all knew that outside the classroom students were exposed to new texts and resources, whereas in the traditional classroom paper and pencil were the primary tools used for the purpose of conveying messages. These findings are consistent with those of a number of researchers (Hughes & Narayan, 2009;Thompson, 2008;Vasudevan, Schultz, & Bateman, 2010); Specifically, the teachers' comments revealed their perception that students were more likely to participate actively in collaborative projects and reflective learning practices, demonstrating the essential features of willingness and enthusiasm.…”
Section: Teaching Multimodal Composition and Affective Engagementsupporting
confidence: 80%
“…but by relatively mundane forms of information retrieval" (p. 92): the antithesis of design. Notwithstanding a substantial research literature that documents and celebrates some youth designfully expressing a digital "voice" to personally and socially transformative effects (e.g., Alvermann, 2008;Hull, 2003;Hull & Katz, 2006;Pleasants, 2008;Vasudevan, Schulz, & Bateman, 2010), we see that the multimedia texts young people create can often be mere assemblages of words, images and other resources casually appropriated online via some hastily chosen search terms and a few mouse clicks.…”
Section: Introductionmentioning
confidence: 99%
“…As Vasudevan et al (2010) found, when given the opportunity to work outside of the school space and to bring students' out-of-school lives into school projects, students were able to resist dominant notions of success. Therefore, I argue that both practitioners' and scholars' conceptions of inquiry, engagements with texts, and social responsibility practices must be widened.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…In outlining such precise steps for the research stage of inquiry (New York City School Library System, n.d., p. 21), for example, the standards suggest that students may be deemed successful inquirers if they merely complete inquiry assignments by finding the right answers. However, these narrowly focused assignments might not be inclusive of student knowledge, heritage, and interests (Vasudevan, Schultz, & Bateman, 2010). Consequently, the funds of knowledge (Esteban-Guitart & Moll, 2014) and interests that these students bring to the library may not be recognized.…”
Section: Standard 1: Using Inquiry To Build Understanding and Create mentioning
confidence: 99%